MENINGKATKAN HASIL BELAJAR PKN MATERI SEMANGAT DAN KOMITMEN KEBANGSAAN MELALUI PEMBELAJARAN KOOPERATIF JIGSAW DI MTSN MEUREUBO - Fatriana, Fatriana (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2022)
Civics learning for class VIII-2 MTsN Meureubo Kab. West Aceh in the even semester of the 2021/2022 academic year has not shown satisfactory results. The minimum learning completeness score that must be achieved is 70, however, only 45% of students are able to achieve a KKM score of 70. In other words, 55% of students, the final grade of study is below the KKM. This type of research is CAR which consists of two cycles, each cycle consists of 2 x meetings. The research subjects were students of class VIII-2 MTsN Meureubo Kab. Aceh Barat, totaling 20 people consisting of 11 men and 9 women. The data collection instruments in this study were tests, observations, and discussions. The results of observations of student activities in learning during the first cycle reached an average value of 66.2, the teacher's activity in teaching and learning activities in the first cycle was in the sufficient category with a score of 55 or 78.5%. While the ideal score is 70. This happens because they stand in front of the class more and provide less direction to students how to do cooperative learning. Learning outcomes for learning materials from the ideal score of 100, the average acquisition score only reached 63 or 63.1%. The results of observations of student activities in PBM during the second cycle reached an average value of 74.3, The results of observations of teacher activities in PBM in the second cycle were classified as moderate. This means that it has improved from the first cycle. From the ideal score of 70, the value obtained is 68 or 97.1%. Student learning outcomes on learning materials in the second cycle are also classified as moderate, namely from this the ideal score of 100 the average score of acquisition is 71 or 71%. Based on the results of this study, it can be said that the application of the Jigsaw type cooperative approach is one of the elaboration strategies that can improve Civics learning outcomes for the subject of National Spirit and Commitment to class VIII-2 MTsN Meureubo Kab. West Aceh.